Find me! An indoor location system - Martinho, Stuart Costa (2019)
This work presents an approach of combining location information from beacons and local building information to give location and guidance to a user inside a complex building. This information can help user’s orientation into unknown buildings through a smartphone. Beacons are installed on the building and emit signals that are converted to user current position, related with Bluetooth’s range. The building data is generated by Building Information Modeling (BIM) model which is going to be used as input data of this project. This system is based on a mobile App (Find Me!), for Android OS (Operating System), which captures the Bluetooth Low Energy (BLE) signals, coming from the beacon(s), and shows, through a map, the location of the user ‘s smartphone, and his destination, and guides him to the desired destination.